Shelter - "Haycock, Kate" (Wayland Publishers Hove, 1993)
The book "Shelter" by Kate Haycock, published in 1993 by Wayland Publishers. This 48-page hardcover is part of the "Human Rights" series and is suitable for middle primary to junior secondary students. The book investigates global homelessness, examining its causes and the efforts of various organizations to address the issue. It encourages readers to consider why adequate shelter remains unattainable for many and is illustrated with color and black-and-white photographs.